Citrus Exocortis Viroid - Durán-Vila, Núria (Elsevier, 2020)
Citrus exocortis viroid, belonging to the genus Pospiviroid of the family Pospiviroidae, is the causal agent of the exocortis disease. It has also been reported to affect tomato, grapevine, and certain ornamental species. It has a wide natural and experimental host range, mostly composed of symptomless viroid–host combinations. This chapter reports its transmission, epidemiology, and economic impact, as well as the available measures for its detection and control.